Analysis of Job Promotions to Improve the Performance of Bombana Regency Civil Servants - Imam Hanafi; Tegar Imam Anwar; Dewi Endah Wigati (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2024)
Bombana Regency became an autonomous region based on Law Number 29 of 2003 concerning establishment in Southeast Sulawesi Province. The development of a region is highly dependent on the competence and participation of the human resources in utilizing the potential of respective areas. Therefore, the development of human resources is essential to support future development process. However, the Regional Staffing Agency (BKD) of Bombana Regency faced several challenges. The implementation of objective competency tests has not been optimal, and employees performance is hindered by inadequate Manpower Planning (workforce planning in accordance with organizational needs through identification, evaluation and needs planning). The execution of employees education and training (Diklat) has not been carried out effectively. Therefore, this study aimed to investigate the challenges to promotions affecting the performance of civil servants at the BKD of Bombana Regency and explore the efforts to address these issues. Qualitative and quantitative methods were used, in-depth interviews were conducted with key informants, and descriptive statistics were derived from processed questionnaires. Furthermore, data were collected through interviews, observation, and documentation. The results showed that subjectivity was a significant challenge that affected promotions considerations and employees performance at BKD Bombana Regency. The primary effort to address this issue and improve employees performance was the implementation of competency tests.